Leucaena leucocephala, White Leadtree - Michael G. Andreu; Melissa H. Friedman; Robert J. Northrop (EDIS)
In Florida, white leadtree is a prohibited species and therefore is not used in commercial applications in the state. However, in its native range, it is used as a source of charcoal, fuel, and lumber. It has also been planted as a windbreak for crops such as coffee and cocoa, and some ranchers use the tree as a source of both shade and forage for cattle, with the pods being an excellent source of protein. In addition, as white leadtree forms a well-developed taproot, it has been planted to assist with erosion control. This 2-page fact sheet was written by Michael G. Andreu, Melissa H. Friedman, and Robert J. Northrop, and published by the UF Department of School of Forest Resources and Conservation, July 2012.